Bahasa Indonesia untuk Penutur Asing: Mengoptimalkan Pembelajaran BIPA dengan Aplikasi Digital - Zira, Khairana; Noor, Muhammad El Fahrizi; Siringoringo, Natalia Debriyanti; Sitohang, Olly Risfa; Harahap, Safinatul Hasanah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In the current era of modernization, digital applications have brought revolutionary changes in the way we acquire knowledge and skills, including language learning. Seeing the large number of uses of digital applications for language learning today, the author is interested in discussing the use of tandem applications in learning Indonesian for foreign speakers. In this research, qualitative descriptive research is aimed at describing and illustrating existing phenomena, both natural and human engineered, which pays more attention to characteristics, quality, and interrelationships between activities. The subjects of this research are foreigners who have joined or used the Tandem application which connects language learners with native speakers. The material taught is BIPA level A1 learning where students can use Indonesian in daily communication. Then, data collection in this research used primary data collection techniques. This research shows that the use of BIPA (Indonesian for Foreign Speakers) with digital applications has the potential to provide great benefits in expanding access and increasing the effectiveness of Indonesian language learning for foreign learners. This shows that the optimal use of digital applications in learning foreign languages can make a significant contribution to Indonesian language learning at the international level.